2015
DOI: 10.1007/s11128-015-1121-y
|View full text |Cite
|
Sign up to set email alerts
|

Classification of two-qubit states

Abstract: Verstraete, Dehaene and DeMoor showed that each of the two-qubit states can be generated from one of two canonical families of two-qubit states by means of transformations preserving the tensor structure of the state space. Precisely, each of such states can be generated from a three-parameter family of Bell-diagonal states or from three-parameter rank-deficient states. In this paper, we show that this classification of two-qubit states can be refined. In particular, we show that the latter canonical family of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…We have extended an introductory analysis of this orbit given in [3]. In particular, we have explicitly calculated entanglement of formation and quantum discord for all states from the considered SLOCC orbit of rank-deficient two-qubit states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have extended an introductory analysis of this orbit given in [3]. In particular, we have explicitly calculated entanglement of formation and quantum discord for all states from the considered SLOCC orbit of rank-deficient two-qubit states.…”
Section: Discussionmentioning
confidence: 99%
“…Classification of all two-qubit states into orbits with respect to transformations (3), so-called SLOCC orbits, was considered in [2]. In our previous work [3] we have refined this classification. In [2,3] it was shown that each of two-qubit states can be generated from one of the following distinct states:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the proof is done for any root ξ = 0 but the statement also holds in the case of ξ = 0 and its corresponding antipodal point ξ = ∞: Let us suppose that the constant term in p (σ) ρ (ζ) is zero, and hence there is a root ξ = 0. The hermiticity property (33) implies that the coefficient of the highest exponent ζ 2σ is also zero, implying that p…”
Section: A T -Representationmentioning
confidence: 99%
“…In our previous work 10 we studied the explicit constructions of separable two qubits density matrices based on the study of Lorentz transformations developed by Verstraete et al 4 6 − Following this approach an arbitrary two qubits state can be written in the form ( ) ( ) real. Detailed analysis for the two qubits density matrix which is of the form (1.4) has been given by Caban et al 11,12 Verstraete et al, 4 6 − have shown that the 4 4 × matrix , R µ ν can be written as 1 Then, for this special case we get:…”
Section: Introductionmentioning
confidence: 98%